Urinary levels of interleukin-6 and interleukin-8 in patients with vesicoureteral reflux and renal parenchymal scar - TOPUZOĞLU, AHMET; DEDE, FUAT; ALPAY, HARİKA; GÖKCE, İBRAHİM (SPRINGER, 2010)
The objective of this study was to assess the urine levels of interleukin-6 (IL-6) and interleukin-8 (IL-8) as noninvasive markers of vesicoureteral reflux (VUR) and renal parenchymal scarring (RPS) in children in the absence of a recent urinary tract infection (UTI) episode. Urine concentrations of IL-6 and IL-8 in 114 children aged 1 month to 16 years were evaluated. The children were divided into four groups: group 1, 26 children with VUR and RPS; group 2, 27 children with VUR without RPS; group 3, 34 children with RPS without VUR, group 4, 27 children without VUR and RPS, as the control group. After the first assessment, the children were divided into four larger groups for comparison purposes: group A (groups 1+2), 53 children with VUR; group B (groups 3+4), 61 children without VUR; group C (groups 1+3), 60 children with RPS; group D (groups 2+4), 54 children without RPS. Urinary IL-6 and IL-8 concentrations were determined. To avoid dilution effects and to the standardize samples, urinary levels of IL-6 and IL-8 were expressed as the ratio of cytokine to urinary creatinine (pg/mg). The median urine IL-6/creatinine was significantly higher in patients with VUR than in those without VUR (5.72 vs. 3.73). In patients with VUR, there was a significant but rather weak correlation between IL-6/creatinine concentrations and the reflux grade (p < 0.05, R = 0.305). The median urine IL-8/creatinine was significantly higher in patients with RPS than in those without RPS (43.12 vs. 16.36). In patients with RPS, there was a significant but rather weak correlation between IL-8/creatinine concentrations and the renal scar grade (p < 0.05, R = 0.251). The results of this study provide preliminary evidence that children with VUR have a high urine IL-6 concentration, whereas children with RPS have a high urine IL-8 concentration.
Keywords: Interleukin-6; Interleukin-8; Reflux nephropathy; Urinary tract infection; Vesicoureteral reflux; TRACT-INFECTION; CHILDREN; PYELONEPHRITIS; SCINTIGRAPHY; SERUM